Exploring Cartagena's tourism industry: Insights from my internship at Corpoturismo (2024)
Before starting my internship, I established several objectives to guide my development process within the internship site, as well as to ensure a meaningful experience. The most important one was to develop more communication skills, as in this new experience I was going to interact with a wide variety of people, including tourists and professionals in the tourism sector, very different from what I was used to in my academic environment. This objective was complementary to that of applying all the knowledge about foreign languages acquired throughout the academic formation. I also focused on learning about the functioning of the tourism industry in Cartagena and gaining a deeper understanding of its processes and dynamics, as this was a completely new subject for me. Therefore, working in the entity in charge of promoting tourism in the city represented a great opportunity. Finally, on a more personal level, I set out not only to fulfil my job responsibilities, but also to fully enjoy the whole experience. I committed myself to give my best to ensure success in all tasks and to always be ready to offer the necessary support to the entity. Being this my first entry into the working world, I wanted to make the most of it.